The Influence of Distinctive Capability and Innovation Management Towards the Performance of ISPs in Indonesia - CHRISTIADI, Henry; SULE, Ernie Tisnawati; SURYANA, Yuyus; FEBRIAN, Erie (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The growing need for Internet influence the growing number of ISPs (Internet Service Provider) companies in Indonesia. Until the end of 1999, there were about 55 operating and non-operating ISPs companies in Indonesia. In 2001, its number increased to 155 companies and per 31 December2016 became 302 companies. However, there is still dissatisfaction from its users to the services received. It does not lead to optimal profitability growth of optimal. Some of them were in the range between 10% - 20% and only some of them were in the range between 30% - 40%. This condition is caused by some problems in innovation management and the development of distinctive capabilities development of companies. Thus, the purpose of this study is to investigate the influence of distinctive capabilities and innovation management on the performance of ISP companies in Indonesia. It was conducted to100 ISP companies in Indonesia in 2017, which were chosen as samples and analyzed using PLS. The results showed that the distinctive capabilities and innovation management influenced on the performance of ISP companies in Indonesia, which is innovation management, gave more dominant influence.